Особливості утримання та розмноження Theodoxus fluviatilis (Gastropoda, Pectinibranchia, Neritidae) в умовах лабораторного акваріума - Тарасова, Юлія; Tarasova, Yuliya (Східноєвропейський національний університет імені Лесі Українки, 2014)
Встановлено оптимальні умови утримання Theodoxus fluviatilis (Gastropoda, Pectinibranchia, Neritidae), з’ясовано терміни настання статевої зрілості цих молюсків та особливості утворення кладок в умовах лабо¬раторного акваріума. The article deals with the optimal conditions of Theodoxus fluviatilis (Gastropoda, Pectinibranchia, Neritidae) with the requirements to the substrate, the temperature and hardness of water, light and aeration, feeding ration. The size-age gradation of mollusk shells, the timing of sexual maturity and features of the oviposition in the condition of laboratory aquarium were analyzed.
The Features of Keeping and Cultivation Theodoxus fluviatilis (Gastropoda, Pectinibranchia, Neritidae) in a Laboratory Aquarium
Keywords: молюски; Theodoxus fluviatilis; акваріумне утримання; розведення; кладки; Theodoxus fluviatilis; substrate; feeding ration; the size-age gradation of mollusk shells; cultivation; oviposition